Neo-clerodane diterpenoids from aerial parts of Salvia hispanica L. and their cardioprotective effects. (October 2019) - Fan, Min; Luo, Dan; Peng, Li-Yan; Li, Xiao-Nian; Wu, Xing-De; Ji, Xu; Zhao, Qin-Shi
Abstract: Ten undescribed neo -clerodane diterpenoids, named hispanins A-J, together with six known ones, were isolated from the aerial parts of Salvia hispanica L . Their structures were established by extensive spectroscopic analysis. The absolute configurations of the undescribed compounds were determined by the ECD data and single crystal X-ray diffraction analysis. Hispanins B and C represented the first neo -clerodane diterpenoids with a unique oxygen bridge between C-19 and C-20. All isolated compounds were evaluated for their protective effects against H2 O2 -induced cardiomyocyte injury. Five of these compounds showed significant cardioprotective effects. Graphical abstract: Ten undescribed neo -clerodane diterpenoids together with six known ones were isolated from the aerial parts of Salvia hispanica L . Five of these compounds showed significant cardioprotective effects.Image 1 Highlights: Ten undescribed diterpenoids were obtained from Salvia hispanica L. The absolute configurations of eight compounds were confirmed by X-ray diffraction. Two undescribed diterpenoids were elucidated by ECD data analysis. Five compounds exhibited cardioprotective activities.